EVALUATION OF CIVIC EDUCATION LEARNING PROGRAM IN BUILDING THE FIFTH-GRADE STUDENTS’ CHARACTER AT SD NEGERI JUMO DURING THE TRANSITION - Arum Wahyu Damayanti; Hesti Sadtyadi; Widia Darma (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the success or failure of the implementation of civic education learning programs that implement character values. The assessment was carried out by analyzing the Context, Input, Process, and Product for the implementation of the civic education learning program in class 5 at SD Negeri Jumo. The research was conducted from October to February 2022 to 2023. The research is evaluation research with a qualitative approach using the CIPP model. The research results indicate that context, seen from the vision, mission, school goals, syllabus, strategies, and programs, is appropriate and supports character building. Input is also based on the background of the teachers, students, facilities/infrastructure, formulation of lesson plans, and teaching materials that are appropriate in supporting the learning process so that the learning process can be carried out properly. The process is in the form of implementing civic education learning in which the teacher has carried out according to the lesson plans, in the implementation, the right methods/strategies, tools/media, and teaching materials have supported character education. The product has been achieved enough well, where students already have character values such as applying 5S (smile, greeting, greeting, being polite and courteous), cooperation, mutual cooperation, etc, and can apply them in everyday life. The process of civic education learning programs can be said to succeed as seen from students’ product data.